Influence Service Quality and Product Quality Towards Customer Satisfaction Through Purchasing Decisions At Kajan Bento Restaurant In Karawang Regency, West Java Province - Aprianti, Chella; Razak, Ismail; Rejeki, Dewi (Indonesian Journal Economic Review (IJER), 2026)
This study aims to analyze the effect of service quality and product quality on satisfaction through customer purchasing decisions at Kajan Bento Restaurant, Karawang Regency. The respondents of this study were customers of Kajan Bento Restaurant in Karawang Regency, West Java Province. The data analysis techniques used were descriptive analysis and path analysis. The results of the study indicate that service quality and product quality have a positive and significant effect on the purchasing decisions of customers at Kajan Bento Restaurant in Karawang Regency, West Java Province. Service quality and product quality have a positive and significant effect on customer satisfaction at Kajan Bento Restaurant in Karawang Regency, West Java Province. Customer satisfaction has a positive and significant effect on the purchasing decisions of customers at Kajan Bento Restaurant in Karawang Regency, West Java Province. service quality and product quality have a positive and significant effect on customer satisfaction through the purchasing decisions of Kajan Bento Restaurant customers in Karawang Regency, West Java Province.